Pemberdayaan Lahan dan Potensi Pertanian di Desa Batuah, Kecamatan Basarang, Kabupaten Kapuas, Kalimantan Tengah: Land Empowerment and Agricultural Potential in Batuah Village, Basarang District, Kapuas Regency, Central Kalimantan - Yanetri Asi Nion; Fitria Husnatarina; Nesa Cristia; Yarni Hulu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Since 2021, the government has been developing a food estate program at the Desa Batuah, clearing many hectares of rice fields. The problems faced by the community are frequent flooding in the planting area, low pH, and attack of the plant by pests, disease, and weeds that reduce agricultural production. The purpose of community service in this activity is the Batuah Village community and Real Work Lecture-Nationality students who at that time served in Batuah Village were able to explain land empowerment and village agricultural potential and were skilled in carrying out land empowerment, overcoming the problem of nuisance organisms plants and recognize the agricultural potential in the village and then maximize its potential. Empowerment of agricultural land in Batuah Village needs to pay attention to the keys to successful management of tidal swamp land for sustainable agriculture, such as Water Management, Land arrangement, Adaptive and prospective commodity selection, and application of suitable cultivation technology. Few farmers (10%) still need to apply technology to overcome agricultural problems in Batuah Village. The community recognizes the superior potential plant of Batuah Village, such as rimbang Dayak (hairy-fruited eggplant, Solanum lasiocarpum), celery, and bamboo, but this potential has yet to be maximized. Rimbang still needs to be widely used as processed food and mostly only as vegetables for the community. The team and Real Work Lecture-Nationality students succeeded in maximizing the potential of rimbang by processing rimbang into syrup and jam to increase the economic income of the Batuah village community.